Behavioral analysis of students’ login credentials management in mobile environment - Katuk, Norliza; Halim, Mohamad Subri; Mohamad Tahir, Hatim; Ahmad, Amran; Mat Yusof, Sharmila (2013)
The number of password-protected Internet-based applications is increasing significantly compared to a decade ago.Consequently, it causes an increase in the number of login credentials that users have to manage, for both Internet ad mobile environments. This paper presents a study that specifically focused on students’ login credential management for mobile computing users.A behavioral study was conducted on 250 students from Universiti Utara Malaysia to understand how they managed their login credential while accessing the Internet via their mobile devices.The results suggested that students practiced poor login credential management.The paper recommends approaches that can be taken to improve login credential management for users with mobile devices.